2000
DOI: 10.1093/humrep/15.suppl_2.160
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal non-disjunction in human oocytes: is there a mitochondrial connection?

Abstract: The frequency of chromosome abnormalities due to non-disjunction of maternal chromosomes during meiosis is a function of age, with a sharp increase in the slope of the trisomy-age curve between the ages of 30 and 40 years. The basis of this increase, which is a major cause of birth defects, is unknown at present. In recent years, mutations in mitochondrial (mt) DNA have been associated with a growing number of disorders, including those associated with spontaneous deletions of mtDNA (deltamt DNAs). Intriguingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 80 publications
3
57
1
1
Order By: Relevance
“…The same mechanism has been postulated to play a role in the ageing of human oocytes [143][144][145][146][147][148][149]. Considering that human oocytes enter the first stage of meiosis during fetal life and then arrest until later in adult life, when they are selected for further development via folliculogenesis, this long period of quiescence might be responsible for the sustained exposure of the oocyte in general and its mitochondria in particular to ROS, with the resultant compromise in the capacity of the oocyte to finish the process of meiosis competently [150].…”
Section: Menopausementioning
confidence: 71%
“…The same mechanism has been postulated to play a role in the ageing of human oocytes [143][144][145][146][147][148][149]. Considering that human oocytes enter the first stage of meiosis during fetal life and then arrest until later in adult life, when they are selected for further development via folliculogenesis, this long period of quiescence might be responsible for the sustained exposure of the oocyte in general and its mitochondria in particular to ROS, with the resultant compromise in the capacity of the oocyte to finish the process of meiosis competently [150].…”
Section: Menopausementioning
confidence: 71%
“…As mitochondrial function is essential for both oocyte and embryonic development (Cummins 2004, Eichenlaub-Ritter et al 2011), it appears that the significantly reduced functional mitochondria in the oocytes recovered from women of advanced reproductive age underlines the impairment of oocyte developmental competence (Madankumar et al 2003) by bioenergetic deficiencies, resulting in chromosomal segregation disorders (Schon et al 2000), failed maturation and fertilisation (Reynier et al 2001), and arrested cellular development (Van Blerkom 2011). However, our observation contrasts with a previous study (Duran et al 2011), which may be due to a difference in the mitochondrial assessment technique used.…”
Section: Discussionmentioning
confidence: 99%
“…Whether a similar situation can occur in the human owing to high levels of ATP generation (Van Blerkom et al 1995) that may be associated with unusually high mitochondria/mtDNA copy numbers warrants further study. The importance of this research would be demonstrated if meiotic spindle defects and errors in chromosomal segregation that result in lethal aneuploidies and other chromosomal disorders common in human oocytes and early embryos could be directly associated with differences in mitochondrial complement size, mtDNA copy numbers and cytoplasmic mechanisms that regulate mitochondrial activity (Schon et al 2000, Dumollard et al 2004, EichenlaubRitter et al 2004.…”
Section: Mitochondria As Metabolic Forces In Early Developmentmentioning
confidence: 99%